2012
DOI: 10.1158/0008-5472.can-12-1949
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Metabolic Reprogramming through Lactate Shuttle Coordinately Influences Tumor-Stroma Interplay

Abstract: Cancer-associated fibroblasts (CAF) engage in tumor progression by promoting the ability of cancer cells to undergo epithelial-mesenchymal transition (EMT), and also by enhancing stem cells traits and metastatic dissemination. Here we show that the reciprocal interplay between CAFs and prostate cancer cells goes beyond the engagement of EMT to include mutual metabolic reprogramming. Gene expression analysis of CAFs cultured ex vivo or human prostate fibroblasts obtained from benign prostate hyperplasia reveale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
390
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(410 citation statements)
references
References 47 publications
20
390
0
Order By: Relevance
“…Consistent with the findings from Fiaschi et al (2012), we also demonstrated that microenvironment, represented by fibroblasts, strongly affects tumor metabolism and growth capacity. In particular, we demonstrated that primary fibroblasts and tumor cells establish reciprocal metabolic changes.…”
Section: Sdh Deficiency and Cell Metabolismsupporting
confidence: 91%
“…Consistent with the findings from Fiaschi et al (2012), we also demonstrated that microenvironment, represented by fibroblasts, strongly affects tumor metabolism and growth capacity. In particular, we demonstrated that primary fibroblasts and tumor cells establish reciprocal metabolic changes.…”
Section: Sdh Deficiency and Cell Metabolismsupporting
confidence: 91%
“…38 Then, it was demonstrated that stromal cells may perform aerobic glycolysis under the influence of tumor cells and donate lactate to feed OxPhos metabolism of tumor cells, the so-called "Reverse Warburg Effect." [39][40][41] Metformin, a drug that is found to be effective in tumors, [42][43][44][45] when it was added in acidic medium, which will be used for MSC conditioning, blocks TGFb expression and reverts inhibition of GLUT 1 and 3 elicited by acidic medium in MSC. Moreover, melanoma cells conditioned by LpH-metformin-treated MSC medium exhibited a reconstituted epithelial-like profile and a reduced invasion, that were associated with a reduction of GLUT 1, 3.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET cannot be used to detect primary tumors; reviewed in [124,125]) suggest that other substrates are fueling cancer growth. Specifically, a lactate-shuttle between cancer-associated fibroblasts and tumor-tissue was proposed [126], since cancer-associated fibroblasts express the monocarboxylate transporter 4 and tumors overexpress the monocarboxylate transporter 1 (reverse Warburg effect) [127][128][129][130]. This relationship allows the tumor to take up lactate and to convert it to pyruvate, which is processed in the tricarboxylic acid cycle.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…This suggests that a substantial portion of the glucose taken up is channeled through the pentose phosphate pathway for reduction of NADP + and consequently glutathione disulfide, as well as for de novo nucleotide biosynthesis [168,169]. Besides, prostate cancer still relies on oxidative phosphorylation, which is enforced by the interaction with cancer-associated fibroblasts as shown for PC-3 cells [127]. Consistently metformin, an inhibitor of mitochondrial complex I, provokes a decrease of proliferation with a subsequent activation of reductive glutamine metabolism in vitro and in a TRAMP mouse model [159,170].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%